2005
DOI: 10.1038/sj.bjp.0706250
|View full text |Cite
|
Sign up to set email alerts
|

Anticonvulsant enaminones depress excitatory synaptic transmission in the rat brain by enhancing extracellular GABA levels

Abstract: 1 Enaminones are a novel group of compounds that have been shown to possess anticonvulsant activity in in vivo animal models of seizures. The cellular mechanism by which these compounds produce their anticonvulsant effects is not yet known. This study examined the effects of enaminones on excitatory synaptic transmission. 2 We studied the effects of 3-(4 0 -chlorophenyl)aminocyclohex-2-enone (E118), methyl 4-(4 0 -bromophenyl)aminocyclohex-3-en-6-methyl-2-oxo-1-oate (E139) and ethyl 4-(4 0 -hydroxyphenyl)amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
48
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 47 publications
4
48
0
Order By: Relevance
“…The subcutaneous pentylenetetrazol seizure model identifies compounds that inhibit the GABA antagonistic effects of pentylenetetrazol or raise the seizure threshold (Stables and Kupferberg, 1997). Studies have shown that a number of enaminone compounds display inhibition against glutamate-mediated excitatory synaptic transmission by modulation of GABAergic transmission (Kombian et al, 2005;Ananthalakshmi et al, 2006). Based on the above findings and the results we present, we hypothesize the existence of an essential pharmacophore within the enaminone structure that possibly interacts with the GABA receptor, which is significant for achieving anticonvulsant activity.…”
Section: Discussionmentioning
confidence: 50%
See 4 more Smart Citations
“…The subcutaneous pentylenetetrazol seizure model identifies compounds that inhibit the GABA antagonistic effects of pentylenetetrazol or raise the seizure threshold (Stables and Kupferberg, 1997). Studies have shown that a number of enaminone compounds display inhibition against glutamate-mediated excitatory synaptic transmission by modulation of GABAergic transmission (Kombian et al, 2005;Ananthalakshmi et al, 2006). Based on the above findings and the results we present, we hypothesize the existence of an essential pharmacophore within the enaminone structure that possibly interacts with the GABA receptor, which is significant for achieving anticonvulsant activity.…”
Section: Discussionmentioning
confidence: 50%
“…Another anticonvulsant enaminone, E139 (Fig. 2), was reported to suppress excitatory synaptic transmission by enhancing extracellular GABA levels (Kombian et al, 2005) and blocking tetrodotoxin-sensitive sodium channels and, thereby, directly inhibiting postsynaptic neuronal excitability . Meanwhile, several enaminones with chemical moieties different from KRS-5Me-4-OCF 3 were described to interact with GABA A receptors (Reitz et al, 1999;Yohannes et al, 2003;Hogenkamp et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations